A new metabolite of Paricalcitol: stereoselective synthesis of (22Z)-isomer of 1α, 25-dihydroxy-19-norvitamin D2. Issue 12 (23rd March 2016) - Samala, Ramakrishna; Sharma, Somesh; Basu, Manas K.; Mukkanti, K.; Porstmann, Frank
Graphical abstract: Abstract: Stereoselective synthesis of (22 Z )-isomer of Paricalcitol, an analog of 1, 25-dihydroxyergocalciferol, an active form of vitamin D2 (Ergocalciferol) has been described. The two key critical synthetic steps involved are Julia–Lythgoe's Wittig–Horner coupling of aldehyde functionality of CD-ring system with benzothiazolyl sulfone, and Horner–Wadsworth–Emmons reaction of phosphine oxide with a Windaus–Grundmann's ketone to build a diene motif between the A and CD-ring system of Paricalcitol.